First insights into the phylogeny of the subgenus Cryobius Chaudoir, 1838 (Coleoptera: Carabidae: Pterostichus) - Sedlmeier, Jan Erik; Faille, Arnaud (Senckenberg Gesellschaft für Naturforschung, 2022)
The past climatic changes caused repeated distribution shifts within insect populations leading to a highly diverse fauna in the mountain regions, which have acted as a refuge for many groups. There, some taxa have adapted to high altitudes and cold climatic conditions. One of those is the highly diverse and Holarctic subgenus Cryobius Chaudoir, 1838 (Carabidae: Pterostichus) including both locally and widely distributed species. Isolated and morphologically divergent populations of the same species led to the description of many subspecies. Until now, there has been no comprehensive work concerning the phylogeny of Cryobius, and genetic data on this taxon are sparse. This study is the first to provide insights into the molecular phylogeny of this subgenus, focusing on species from the Pyrenean and Cantabrian mountain systems. Cryobius specimens were sequenced targeting mitochondrial and nuclear genes. A molecular phylogeny was then built, merging the new data with genetic data from online public databases. All species of Cryobius included in this study form a monophyletic clade within Pterostichus. The synonymy of the two former taxa Pyreneorites and Haptoderus with Cryobius is confirmed by this study. Cryobius of the Pyreneo-Cantabrian area are closely related. Moreover, several well-supported clades of local species were found. The results further indicate a relation between Nearctic and Eastern Palearctic Cryobius, in agreement with the theory of faunal and floral colonization of North America via the Bering land bridge.